Organocatalyzed Oxa-Diels–Alder Reactions: Recent Progress - Biswas, Anup; Kundu, Samrat; Pal, Dhananjoy; Pal, Amit; Maji, Modhu Sudan (Synthesis, 2021)
The oxa-Diels–Alder reaction is a straightforward, atom-economical process for the construction of six-membered oxacycles, which are privileged structures due to their very common occurrence in several pharmaceuticals and natural products. As with many other asymmetric transformations, organocatalysis provides an elegant pathway to their synthesis via [4+2] annulation under mild reaction conditions. The oxa-Diels–Alder reaction utilizes either an α,β-unsaturated carbonyl as an oxa-diene with a suitable dienophile or a simple carbonyl as a dienophile with other dienes. A range of organocatalysts has been explored in the past decade to execute this strategy. The catalysts induce stereoselectivities via two basic reactivities: (1) The formation of chiral intermediates, or (2) selectively activating suitable reactants via a transition state. The present short review compiles organocatalyzed asymmetric oxa-Diels–Alder reactions published over the last ten years, along with detailed discussions on mechanistic approaches.1 Introduction2 Catalysis through Covalent Activation2.1 N-Heterocyclic Carbenes2.2 Amines2.3 Isothiourea Catalysis2.4 Phosphines3 Catalysis through Non-Covalent Activation3.1 Bifunctional Amines3.2 Brønsted Acids3.3 Guanidines4 Multicatalysis through Both Covalent and Non-Covalent Activation5 Conclusion
Keywords: Diels–Alder; asymmetric; organocatalysis; oxa-dienes; dienophiles